Class 1 integron element in Thai Acinetobacter baumannii reveals a linkage to the European clone I - Thapa, B; Tribuddharat, C; Srifuengfung, S; Dhiraputra, C (International Journal of Infection and Microbiology, 2012)
BACKGROUND: Class 1 integron element is innate to most of the multidrug resistant Acinetobacter baumannii and its spread is common among international clones worldwide. The aim of this study was to document the presence of blaVEB-1 harboring class 1 integron element and its gene cassettes in Thai A. baumannii in relation to A. baumannii European clone I, AYE strain. MATERIALS AND METHODS: Thirty seven carbapenem resistant A. baumannii isolates identified in routine microbiology laboratory of Siriraj Hospital, Bangkok were studied. The dot blot hybridization was performed to detect class 1 integron element integrase gene. PCR was used to amplify blaVEB-1, arr2, cmlA, blaOXA-10 resistance cassettes, and variable region of class 1 integron element. blaVEB-1 gene was localized by southern blot hybridization. RESULTS: The prevalence of class 1 integron element was 86.48% in the isolates studied. The blaVEB-1 was present in 7 isolates however the location of blaVEB-1 gene was different in different isolate. Four isolates (Ab03-168, Ab04-28, Ab08-20, and Ab08-22) harbored calss 1 integron element variable region sized 5.5 kb as described in strain AYE. However, blaVEB-1 was only amplified from Ab03-168. The cassette organization in this isolate was 5’CS-aadB-blaVEB-1-arr2-cmlA-blaOXA- 10-aadA1-3’CS. The class 1 integron element similar to the element identified in genomic resistance island, AbaRI of European clone I, AYE was identified in Thai A. baumannii. CONCLUSIONS: blaVEB-1 harboring class 1 integron element with minor cassette variation was identified in Thai A. baumanni isolate which might suggest the spread of this resistant cassette or the spread of the European clone I in Thailand. Monitoring of the global spread of multi-resistant A. baumannii is mandatory to control the spread of resistant genes and this multi-resistant pathogen. DOI: http://dx.doi.org/10.3126/ijim.v1i1.6715 Int J Infect Microbiol 2012;1(1):24-28